2003
DOI: 10.1097/01.gme.0000058772.59606.2a
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of osteoporosis and uterine effects in postmenopausal women taking raloxifene for 5 years

Abstract: Five years of raloxifene treatment in healthy postmenopausal women preserves BMD, significantly reduces the likelihood of development of osteoporosis, and was not associated with an increased rate of vaginal bleeding, endometrial hyperplasia, or endometrial carcinoma, compared with the case of placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(56 citation statements)
references
References 33 publications
2
49
0
5
Order By: Relevance
“…In the MORE study which was the largest clinical trial on raloxifene, 7705 postmenopausal women with osteoporosis were treated with raloxifene at a dosage of 60-120 mg/day or with a placebo for 3 years, showed that after 1 year, raloxifene 60 mg/day decreased the risk for new clinical vertebral fractures for 68% compared with placebo in the overall study population and by 60% in women with prevalent vertebral fractures, who are at greater risk for subsequent fractures. Several other studies have demonstrated similar effects of raloxifene on bone loss (12). Raloxifene induces a decreases in biochemical markers of bone turnover that correlate with a subsequent increase in bone mineral density (BMD).…”
Section: Resultsmentioning
confidence: 86%
“…In the MORE study which was the largest clinical trial on raloxifene, 7705 postmenopausal women with osteoporosis were treated with raloxifene at a dosage of 60-120 mg/day or with a placebo for 3 years, showed that after 1 year, raloxifene 60 mg/day decreased the risk for new clinical vertebral fractures for 68% compared with placebo in the overall study population and by 60% in women with prevalent vertebral fractures, who are at greater risk for subsequent fractures. Several other studies have demonstrated similar effects of raloxifene on bone loss (12). Raloxifene induces a decreases in biochemical markers of bone turnover that correlate with a subsequent increase in bone mineral density (BMD).…”
Section: Resultsmentioning
confidence: 86%
“…well documented that treating postmenopausal women or monkeys with HRT increases bone mineral density (27,29,40,41,49,62). However, an increase in bone mineral density is not usually detected until after 1 yr of HRT, and studies examining change in bone mineral density after 6 mo of HRT do not detect an effect (29,62).…”
Section: E764 Estrogen Decreases Body Weight In Monkeysmentioning
confidence: 99%
“…88 In the prevention trials, it was reported that fewer women in the raloxifene treatment group progressed from normal to osteopenia, and from osteopenia to osteoporosis. 89 In addition to its skeletal effects, the MORE trial demonstrates that raloxifene reduces breast cancer by 76% in postmenopausal women with osteoporosis. 90 The recent results of Continuing Outcomes of Raloxifene Evaluation (CORE), the extension arm of the MORE trial, confirm that the breast cancer reduction effect in osteoporotic women lasts up to 8 years, with a reduction rate of 66%.…”
Section: Newer Agents Combination Therapy Selective Estrogen Receptomentioning
confidence: 99%